Eco-innovation determinants in the Brazilian manufacturing industry: an empirical analysis - Ervilha, Gabriel Teixeira; Vieira, Wilson da Cruz; Fernandes, Elaine Aparecida (Economia Aplicada, 2019)
The objective of this paper is to analyze the determinants of eco-innovation in Brazilian transformation industry using the multilevel ordered logit method and the Innovation Research (PINTEC 2014). The results indicated the importance of sectoral heterogeneities in the probability of eco-innovation, besides the individual firm’s factors. In this sense, the strengthening of R&D actions, public investments, the greater interaction between research and teaching institutions with companies and specific regulatory instruments can contribute to having a manufacturing industry more open to efficient environmental management practices.